PENGARUH PERENCANAAN ANGGARAN DAN PENGADAAN BARANG DAN JASA TERHADAP PENYERAPAN ANGGARAN BELANJA - Rini Safitri; Annisa, Annisa (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research aims to examine budget planning and procurement of goods and services on budget absorption. Data collection for this research used a questionnaire. Questionnaires were delivered to 34 employees of the Regional Revenue Agency of West Sumatra Province. This research is included in quantitative research. The sample was determined using total sampling technique. Data analysis uses multiple regression using SPSS 22 software. The results of this research show that budget planning has a positive effect on budget absorption. Procurement of goods and services has no effect on budget absorption.